To total amount of activity….. and beyond: perspectives on measuring physical behavior - Bussmann, Johannes B.; van den Berg - Emons, Rita J. (Frontiers in Psychology, 2013)
The aim of this paper is to describe and discuss some perspectives on definitions, constructs and outcome parameters of physical behaviour. The paper focuses on the following constructs: Physical activity & active lifestyle vs. sedentary behaviour & sedentary lifestyle; Amount of physical activity vs. amount of walking; Detailed body posture & movement data vs. overall physical activity data; Behavioural context of activities; Quantity vs. quality; Physical behaviour vs. physiological response. Subsequently, the following outcome parameters provided by data reduction procedures are discussed: Distribution of length of bouts; Variability in bout length; Time window; Intensity and intensity threshold. The overview indicates that physical behaviour is a multi-dimensional construct, and it stresses the importance and relevance of constructs and parameters other than total amount of physical activity. It is concluded that the challenge for the future will be to determine which parameters are most relevant, valid and responsive. This is a matter for physical behaviour researchers to consider, that is critical to multi-disciplinary collaboration.